2018
DOI: 10.1177/0275074018799487
|View full text |Cite
|
Sign up to set email alerts
|

Organization Performance in Turbulent Environments: The Contingent Role of Administrative Intensity in Hurricane Rita

Abstract: This study uses a natural experiment of school performance during Hurricane Rita in 2005 to investigate the impact of administrative intensity on student achievement in turbulent environments. Administrative intensity constitutes the bureaucratic capacity of the workforce, which we measure as a ratio of noncore to core personnel. Scholars have debated the contingent impact of administrative intensity on organizational performance and policy outcomes—focusing either on its contribution to organizational rigidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…They argued that stability was equivalent to consistency within an administrative system and that an administrative system, by nature, pursued stabilization of the processes of administration. Although the model emphasizes stabilization, only a few scholars have investigated the effects of organizational stability (Meier and O'Toole Jr 2003; Meier, O'Toole Jr, and Hicklin 2010; Ryu and Christensen 2019). To extend our knowledge, the present study examines the manner in which procedural stability, one component of organizational stability, buffers organizations from environmental threats.…”
Section: Understanding the Functions Of Public Management: A Formal M...mentioning
confidence: 99%
“…They argued that stability was equivalent to consistency within an administrative system and that an administrative system, by nature, pursued stabilization of the processes of administration. Although the model emphasizes stabilization, only a few scholars have investigated the effects of organizational stability (Meier and O'Toole Jr 2003; Meier, O'Toole Jr, and Hicklin 2010; Ryu and Christensen 2019). To extend our knowledge, the present study examines the manner in which procedural stability, one component of organizational stability, buffers organizations from environmental threats.…”
Section: Understanding the Functions Of Public Management: A Formal M...mentioning
confidence: 99%
“…Many authors have reiterated that performance cannot be fully understood without accounting for capacity. Hill and Lynn (2005) and Ryu and Christensen (2019) focus on the role of organizational capacity in understanding performance. Thomson and Perry (2006) and Agranoff and McGuire (2001) underscore capacity's role in collaborative or networked performance arrangements.…”
Section: Integrating Performance Management With Context and Capacitymentioning
confidence: 99%
“…Similarly, Andrews et al (2017) showed that the relationship between AI and the performance indexes of universities was inverted U-shaped, suggesting that AI initially generates positive performance outcomes. More recently, Ryu and Christensen (2019) established that AI bears a curvilinear relationship to school performance. However, Andrews et al (2017) argued that the relationship between AI and organizational performance should be investigated in other large entities with smaller central bureaucracies, such as local governments.…”
Section: Citizen Satisfaction and Administrative Intensitymentioning
confidence: 99%